2018
DOI: 10.3389/fphar.2018.01001
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Inhibits Cigarette Smoke-Induced COPD by Attenuating Inflammation and Oxidative Stress via the Regulation of the Nrf2 and NF-κB Signaling Pathways

Abstract: Chronic obstructive pulmonary disease (COPD) is the major leading cause of disease with high-mortality worldwide. Cigarette smoke (CS) is a major factor for COPD. CS causes chronic inflammation and oxidative stress, which contributes to lung dysfunction in COPD. Isoliquiritigenin (ILG), a natural flavonoid derived from the root of liquorice, has been reported to possess antiinflammatory and antioxidant activity. In the present study, we tested the mechanism and protective effects of ILG on CS-induced COPD. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 39 publications
0
34
0
1
Order By: Relevance
“…Even if 7,4ʹ-DHF showed a bit lower IC50 on eotaxin-1 inhibition than that of ILQ, we chose the ILQ as our model drug in the present study. 10 Isoliquiritigenin, a flavonoid compound mainly found in the root of Glycyrrhiza uralensis, had potent antioxidant, 14 anti-inflammatory, [15][16][17] antitumor 18 and antianaphylaxis 10 effects. With a chalcone-type structure, ILQ is easily soluble in several organic solvents and dilute alkaline aqueous solution, but insoluble in water.…”
Section: Introductionmentioning
confidence: 99%
“…Even if 7,4ʹ-DHF showed a bit lower IC50 on eotaxin-1 inhibition than that of ILQ, we chose the ILQ as our model drug in the present study. 10 Isoliquiritigenin, a flavonoid compound mainly found in the root of Glycyrrhiza uralensis, had potent antioxidant, 14 anti-inflammatory, [15][16][17] antitumor 18 and antianaphylaxis 10 effects. With a chalcone-type structure, ILQ is easily soluble in several organic solvents and dilute alkaline aqueous solution, but insoluble in water.…”
Section: Introductionmentioning
confidence: 99%
“…On account of the protective effect on the respiratory system against oxidative lung and airway diseases, Nrf2 could reportedly be an attractive therapeutic target for prevention strategies and clinical therapies in respiratory illnesses [ 46 , 47 ]. It has also been reported that isoliquiritigenin was able to attenuate CS-Induced COPD in mice by inhibiting oxidative stress via the regulation of the Nrf2 [ 48 ]. HO-1, NQO1, and SOD are the antioxidant genes regulated by Nrf2 binding to antioxidant response elements [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke activates NF-κβ within one hour of exposure to the lung thus causing in ammatory reactions which increase white blood cell count, lymphocyte count, and granulocyte count (Churg et al, 2003;Flouris et al, 2012). Data from the pre-clinical study showed 4 weeks of CS exposure signi cantly increased p65 and Iκβα in mice lung as compared to control group (Yu et al, 2018). NF-κβ is also required by IL-1β and IL-17A to induce the expression of MUC5B in bronchial epithelial cells that cause goblet hyperplasia in COPD (Fujisawa et al, 2011).…”
Section: Discussionmentioning
confidence: 99%